Menata Iklim Sekolah yang Kondusif pada Lembaga Pendidikan Agama Islam - Azahra, ‎ Fatma; Junaidi, Junaidi (Institut Teknologi Pendidikan Indonesia, 2022)
This study focuses on school climate which includes the school environment, school rules, principal leadership, and interpersonal relationships. This research is qualitative descriptive research. Data was collected through interviews, observation, and documentation. Data were analyzed through data reduction, data display, and conclusion/verification. The results of the study show that there are four aspects ofschool climate related to school climate conditions, namely aspects of the schoolenvironment which include school cleanliness and orderliness of the school environment, school rules which include school discipline and punishment or sanctions, school principal leadership which includes motivation and cooperation and interpersonal relationships which include a relationship of mutual respect, arelationship of mutual trust, and a relationship of mutual care between school members.